Planet Auschwitz : Holocaust representation in science fiction and horror film and television - Crim, Brian E. (Rutgers University Press, 2020)
"Planet Auschwitz explores the diverse ways in which the Holocaust influences and shapes science fiction and horror film and television by focusing on notable contributions from the last fifty years. The supernatural and extraterrestrial are rich and complex spaces with which to examine important Holocaust themes - trauma, guilt, grief, ideological fervor and perversion, industrialized killing, and the dangerous afterlife of Nazism after World War II. Planet Auschwitz explores why the Holocaust continues to set the standard for horror in the modern era and asks if the Holocaust is imaginable here on Earth, at least by those who perpetrated it, why not in a galaxy far, far away? The pervasive use of Holocaust imagery and plotlines in horror and science fiction reflects both our preoccupation with its enduring trauma and our persistent need to "work through" its many legacies"-- Provided by publisher
Keywords: Holocaust, Jewish (1939-1945), in motion pictures.; Holocaust, Jewish (1939-1945), on television.; Science fiction films -- History and criticism.; Science fiction television programs -- History and criticism.; Horror films -- History and criticism.; Horror television programs -- History and criticism.; Holocauste, 1939-1945, au cinéma.; Holocauste, 1939-1945, à la télévision.; Films de science-fiction -- Histoire et critique.; Émissions de science-fiction télévisées -- Histoire et critique.; Films d'horreur -- Histoire et critique.; Émissions d'horreur télévisées -- Histoire et critique.; HISTORY -- General.; Holocaust, Jewish (1939-1945) in motion pictures; Holocaust, Jewish (1939-1945) on television; Horror films; Horror television programs; Science fiction films; Science fiction television programs; Criticism, interpretation, etc.